LHC Signals of the Next-to-Lightest Scalar Higgs State of the NMSSM in the <svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-0.2725pt" id="M1" height="11.2929pt" version="1.1" viewBox="-0.0657574 -11.0204 16.7185 11.2929" width="16.7185pt"><g transform="matrix(.017,0,0,-0.017,0,0)"><path id="g113-53" d="M456 178V225H360V632H320C217 496 115 347 20 206V178H280V106C280 40 276 34 189 27V0H445V27C364 34 360 39 360 106V178H456ZM280 225H82C149 335 214 431 278 520H280V225Z"/></g><g transform="matrix(.017,0,0,-0.017,8.237,0)"><path id="g113-241" d="M471 456L444 459C426 433 414 430 388 430C324 430 270 434 216 434C103 434 51 374 23 338L43 317C96 366 146 380 221 375L154 109C149 86 147 68 147 52C147 4 168 -12 197 -12C240 -12 291 25 334 71L320 96C295 75 268 58 252 58C238 58 227 79 238 138C251 211 272 296 292 372C310 372 332 368 350 368C391 368 421 369 434 371C444 388 455 413 471 456Z"/></g> Decay Channel - Almarashi, M. M. (Advances in High Energy Physics, 2021)
We study the a1a1 and Za1 decay channels of the next-to-lightest CP-even Higgs boson h2 of the NMSSM at the LHC, where the h2 is produced in gluon fusion. It is found that while the h2 discovery is impossible through the latter channel, the former one in the 4τ final state is a promising channel to discover the h2 with masses up to around 250 GeV at the LHC. Such a discovery of the h2 is mostly accompanied with a light a1, which is a clear evidence for distinguishing the NMSSM from the MSSM since such a light a1 is impossible in the MSSM.